Genipin and EDC crosslinking of extracellular matrix hydrogel derived from human umbilical cord for neural tissue repair - Výborný, Karel; Vallová, Jana; Kočí, Zuzana; Kekulová, Kristýna; Jiráková, Klára; Jendelová, Pavla; Hodan, Jiří; Kubinová, Šárka (Scientific reports, 2019)
Extracellular matrix (ECM) hydrogels, produced by tissue decellularization are natural injectable materials suitable for neural tissue repair. However, the rapid biodegradation of these materials may disrupt neural tissue reconstruction in vivo. The aim of this study was to improve the stability of the previously described ECM hydrogel derived from human umbilical cord using genipin and N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC), crosslinking at concentration of 0.5-10 mM. The hydrogels, crosslinked by genipin (ECM/G) or EDC (ECM/D), were evaluated in vitro in terms of their mechanical properties, degradation stability and biocompatibility. ECM/G, unlike ECM/D, crosslinked hydrogels revealed improved rheological properties when compared to uncrosslinked ECM. Both ECM/G and ECM/D slowed down the gelation time and increased the resistance against in vitro enzymatic degradation, while genipin crosslinking was more effective than EDC. Crosslinkers concentration of 1 mM enhanced the in vitro bio-stability of both ECM/G and ECM/D without affecting mesenchymal stem cell proliferation, axonal sprouting or neural stem cell growth and differentiation. Moreover, when injected into cortical photochemical lesion, genipin allowed in situ gelation and improved the retention of ECM for up to 2 weeks without any adverse tissue response or enhanced inflammatory reaction. In summary, we demonstrated that genipin, rather than EDC, improved the bio-stability of injectable ECM hydrogel in biocompatible concentration, and that ECM/G has potential as a scaffold for neural tissue application.
Keywords: pupečník; Tissue Engineering; Humans; tkáňové inženýrství; Extracellular Matrix; hydrogely; Iridoids; Tissue Scaffolds; extracelulární matrix; lidé; proliferace buněk; Nerve Regeneration; Umbilical Cord; regenerace nervu; iridoidy; karbodiimidy; tkáňové podpůrné struktury; mezenchymální kmenové buňky; Cell Proliferation; Hydrogels; Mesenchymal Stem Cells; Carbodiimides